FITNESS AND BODYBUILDING AS A PHYSICAL ACTIVITY AND ITS IMPORTANCE FOR PHYSICAL DEVELOPMENT, PHYSICAL FITNESS AND MENTAL WELLBEING - Ferenc, Ivana; Oborný, Josef (Advances in Social Sciences Research Journal, 2019)
Nowadays, bodybuilding is already popular amongst the youth to a high degree. It is of great significance that all admirers of this sport are focused in the right direction. In order for a person to get on the right track, there is necessary an excellent teacher to show and teach them the correct way. A properly chosen personal trainer is a first precondition for success, followed by motivation and will of each and every one of us. Bodybuilding as a physical activity has a remarkable importance for physical, mental and aesthetical development of an individual. This sport has greatly contributed to the development of knowledge of body aesthetics, patterns in the field of an athlete’s nutrition and methodology of development of strength and muscle volume.